Cover Feature: Carbamate Synthesis Using a Shelf‐Stable and Renewable C1 Reactant (ChemSusChem 13/2019). Issue 13 (4th July 2019) - Dobi, Zoltán; Reddy, B. Narendraprasad; Renders, Evelien; Van Raemdonck, Laurent; Mensch, Carl; De Smet, Gilles; Chen, Chen; Bheeter, Charles; Sergeyev, Sergey; Herrebout, Wouter A.; Maes, Bert U. W.
Abstract : The Cover Feature shows 4‐propylcatechol carbonate as a new shelf‐stable and renewable C1 reactant for the synthesis of carbamates. It is easily synthesized from 4‐propylcatechol (derived from wood) and dimethylcarbonate (derived from CO2 ) using a reactive distillation system. This research provides a means to prepare carbamates in two steps starting from the cyclic carbonate reactant, that is, substitution with an alcohol followed by an amine, under mild reaction conditions. This order avoids isocyanate intermediates (or their unstable precursors), which are generally considered toxic. 4‐Propylcatechol can be recycled. More information can be found in the Full Paper by Dobi et al on page 3103 in Issue 13, 2019 (DOI: 10.1002/cssc.201900406 ).